Health service delivery limits and alternatives [review of] - Tanga, Catalina R. (Philippine Journal of Public Administration, 1976)
A review of Ivan Illich, Limits To Medicine (London: Marion Boyars Publishers Ltd., 1976) 294 p.; and Peter Wilenski, The Delivery of Health Services in the People's Republic of China (Ottawa: International Development Research Centre, 1976), 59 p.